Wearable monitoring unit for swimming performance analysis - Silva, A. S.; Salazar, A. J.; Borges, C. M.; Correia, M. V. (BIOSTEC 2011, CCIS 73, 2012)
BIOSWIM (Body Interface System based on Wearable Integration Monitoring) is a joint multidisciplinary effort involving a number of Portuguese R&D teams. It seeks a pervasive monitoring solution for physiological and biomechanical signals from a swimmer under normal training conditions, both in and out of the water. A wearable inertial monitoring unit (WIMU) was developed in order to serve as the biomechanical data processing unit of the system. The preliminary version of the WIMU has a commercially available microcontroller and transceiver set, as well as a tri-axial accelerometer and a bi-axial gyroscope serving as sensors. Testing in and out of the water has provided promising data and contributed to design modifications. These also took into account input from athletes, trainers, and physicians. Future work includes the integration of the WIMU within the complete BIOSWIM swimsuit system, complemented by truly integrated EMG and ECG textile sensors and a chemical monitoring unit.